Edaravone dexborneol provides neuroprotective benefits by suppressing ferroptosis in experimental intracerebral hemorrhage - Han Li; Xiang Li; Mingzhi Li; Wenxin Li; Jinghui Wei; Yuming Huang; Haiqing Yan; Juntang Lin; Ping Zhang (Scientific Reports)
Abstract Edaravone dexborneol (EDB) is widely recognized for its anti-inflammatory and antioxidant properties and is clinically applied in the treatment of acute cerebral infarction. Ferroptosis is a critical process in the pathophysiology of brain injury following intracerebral hemorrhage (ICH). However, it remains unclear whether EDB can ameliorate ICH through the modulation of ferroptosis. This study aimed to evaluate the function and mechanism of EDB in treatment of ICH. With a male rat ICH model, animal behavior tests, histopathological staining, magnetic resonance imaging and evans blue staining were used to evaluate the neural protective function of EDB on ICH rats. The potential molecular mechanism was investigated using RNA sequencing. With the administration of Fer-1, a range of ferroptosis-related biomarkers, including Fe2+, 4-hydroxynonenal, malondialdehyde, etc., were analyzed to ascertain whether EDB confers neuroprotective effects through the modulation of P53/GPX4 pathways to inhibit ferroptosis. Finally, the findings were further corroborated using an in vitro ICH model with a P53 inhibitor. EDB has the potential to markedly enhance nerve and motor function, mitigate pathological damage, facilitate hematoma clearance, and repair BBB injury in ICH rats. KEGG analysis revealed that the differentially expressed genes were associated with signaling pathways, including P53 and ferroptosis. Both EDB and Fer-1 substantially reduced the concentrations of Fe2+, 4-hydroxynonenal, malondialdehyde, increased the amount of anti-oxidants, decreased the expression of P53, and concurrently upregulated the expression of GPX4. Besides, the P53 inhibitor PFT-α was observed to significantly reduce the levels of 4-HNE and lipid peroxides, while concurrently increasing the expression of GPX4. This investigation has shed light on the crucial neuroprotective role of EDB by regulating ferroptosis in ICH disease, which provided a theoretical basis for the clinical application of EDB in the treatment of ICH.